Health of Preschool Children and Environmental Factors in Preschool Educational Organization of Bukhara - Самадова Х. С. (Scholars Digest Publishing, 2023)
The purpose of the study is to assess the health of preschool children, factors in a preschool educational institution for the development of preventive recommendations for the preservation and strengthening of children's health.
Keywords: Bukhara, preschool education, children's health, environmental factors.